Strengthening Institutional Capacity of the Hulun Hyang Farmer Group for Advancing the Edelweiss Flower Agroecosystem: a Case Study in Edelweiss Park, Bromo Tengger Semeru National Park, Indonesia - Rahma, Melati Julia; Faronny, Danniary Ismail; Batoro, Jati; Karyawati, Anna Satyana; Putro, Agung Nugroho; Waluyo, Budi (Universitas Diponegoro, 2024)
The escalating demand for Edelweiss flowers as souvenirs due to tourism development threatens their availability and economic value, impacting the indigenous Tengger community, which relies on these flowers for irreplaceable traditional offerings. The Hulun Hyang farmer group was established in 2017 under the guidance of the national park to conserve Edelweiss flowers, and subsequently obtained a cultivation permit from the Ministry of Environment and Forestry. However, the sustainable management of Edelweiss Park necessitates bolstering the group's institutional capacity as a critical agent in its development. This research examines the endogenous growth and active participation of the Hulun Hyang farmer group to strengthen their institutional capacity, enabling the establishment of deeply rooted and locally responsive mechanisms. Community development initiatives aim to foster economically and socially independent communities by enhancing agroecological management capacity by employing a strategic group development approach. Findings indicate that the institutional capacity of farmer groups is directly influenced by member dynamism and participation and indirectly impacted by leadership, member capacities, the role of extension workers, external support, and farmer characteristics. Consequently, efforts to augment the group's institutional capacity focus on promoting member dynamism and active engagement in group activities.